High-frequency coda wave attenuation in the Mid and Far-Western region of the Nepal Himalaya - Kandel, Thakur Prasad; Khanal, Gautam Prashad; Pandey, Krishna (Journal of Nepal Geological Society, 2024)
In this study, we utilized the vertical components seismograms of 111 local earthquakes (Ml 2.5-5.5) recorded at fourteen stations by the HiKNet network, to present the first-ever estimate of the high-frequency coda waves attenuation in the Mid and Far-Western region of Nepal Himalaya. The inverse of coda wave attenuation, Qc (quality factor) is estimated at eight central frequencies of 1.5, 3.0, 6.0, 9.0, 12.0, 15.0, 18.0, and 21.0 Hz through 30 s coda window length by using the single back-scattering model. Our findings are expressed in terms of the (Qc) quality factor, showing a clear frequency-dependent power relation, Qc (f) = Q0 f n where Q0 is Qc at 1 Hz, f is the frequency and n represents the degree of frequency dependence. The estimated average quality factor (Intrinsic and scattering quality factor) of all these seismic stations was obtained asat 30 s coda window length, which represents the highly heterogeneous and seismo-tectonically active region. The relatively lower quality factor (Qc) value was obtained around Bajhang compared to the Mugu and Dailekh seismic belts. The Q0 and n obtained in this study are consistent with previous research in the Central Region of the Nepal Himalaya and results with similar tectonic settings from other seismically active regions.